Ethical considerations in preventive interventions for bipolar disorder. Issue 2 (30th March 2016) - Ratheesh, Aswin; Cotton, Susan M.; Davey, Christopher G.; Adams, Sophie; Bechdolf, Andreas; Macneil, Craig; Berk, Michael; McGorry, Patrick D.
Abstract: Aim: Early intervention and prevention of serious mental disorders such as bipolar disorder has the promise of decreasing the burden associated with these disorders. With increasing early and preventive intervention efforts among cohorts such as those with a familial risk for bipolar disorder, there is a need to examine the associated ethical concerns. The aim of this review was to examine the ethical issues underpinning the clinical research on pre‐onset identification and preventive interventions for bipolar disorder. Methods: We undertook a PubMed search updated to November 2014 incorporating search terms such as bipolar, mania, hypomania, ethic*(truncated), early intervention, prevention, genetic and family. Results: Fifty‐six articles that were identified by this method as well as other relevant articles were examined within a framework of ethical principles including beneficence, non‐maleficence, respect for autonomy and justice. The primary risks associated with research and clinical interventions include stigma and labelling, especially among familial high‐risk youth. Side effects from interventions are another concern. The benefits of preventive or early interventions were in the amelioration of symptoms as well as the possibility of minimizing disability, cognitive impairment and progression of the illness. Supporting the autonomy of individuals and improving access to stigma‐free care may help moderate the potential challenges associated with the risks of interventions. Conclusions: Concerns about the risks of early identification and pre‐onset interventions should be balanced against the potential benefits, the individuals' right to choice and by improving availability of services that balance such dilemmas.